4n-2(1-6n)=94

Simple and best practice solution for 4n-2(1-6n)=94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-2(1-6n)=94 equation:



4n-2(1-6n)=94
We move all terms to the left:
4n-2(1-6n)-(94)=0
We add all the numbers together, and all the variables
4n-2(-6n+1)-94=0
We multiply parentheses
4n+12n-2-94=0
We add all the numbers together, and all the variables
16n-96=0
We move all terms containing n to the left, all other terms to the right
16n=96
n=96/16
n=6

See similar equations:

| 7x-90=580 | | 10x-2-6x=2(2x+4)-1 | | -4(-5p+7)-7=-195 | | 3y-3(5y+5)=-4-5(-4-y) | | -40=5p+10-15 | | 4x+2(x-6)=3(2x-4) | | -4=-9-p-p | | 3x+2+4x=6+5x | | −4x=3(2− | | −4x=3(2− | | −4x=3(2− | | n|5+2=6 | | −4x=3(2− | | −4x=3(2− | | 2x/5=4x/5-20 | | 4z=1264 | | 0.3(z—15)—10.56=15.3 | | 4x–9=15 | | 6(1-4x)+8x=102 | | x=6-(-9) | | 4n+14=16-6n | | 16-8k=-6-2k+10 | | 0.1x+x=89 | | -3(m-8)=0 | | -12x+-9=-105 | | -4+8v=(v-4)-3v | | 1/3(x-7)=1/3x+3 | | 2(h+8.3)-7.94=-1.34 | | 6y=480 | | 5x+15x=20+10 | | 6y+8=6(y+3)−10 | | N=1.2x+0.5 |

Equations solver categories